Large-area two-dimensional polymer nanosheet-based proton exchange membrane and preparation method thereof
By adopting intercalation strategy and combination of polyelectrolytes in two-dimensional polymer nanosheet membranes, the problems of large-area membrane preparation and stability are solved, and large-area two-dimensional polymer nanosheet matrix protons with high proton conductivity and stability are achieved Exchange membrane, suitable for fuel cells and other applications.
Patent Information
- Application Number
- CN202411407175.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-10-10
AI Technical Summary
It is difficult to prepare large-area and stable two-dimensional polymer nanosheet matrix proton exchange membranes, and the inherent characteristics of the nanosheets lead to assembly difficulties and instability, and traditional self-assembly methods limit the area size of the membrane.
Using the intercalation strategy, a large-area 2DP-polyelectrolyte composite membrane was prepared by combining ionic 2DP nanosheets and polyelectrolytes using ultrasound and casting methods to enhance the interaction between nanosheets and enhance the stability of the membrane through acidification treatment. and proton conductivity.
A two-dimensional polymer nanosheet matrix proton exchange membrane with large size (400cm2), high stability and excellent proton conductivity (802 mS cm-1) is achieved, which is suitable for fuel cells and other applications.
Smart Images

Figure CN119144028A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of membrane preparation, and particularly relates to a large-area two-dimensional polymer nanosheet-based ion exchange membrane and a preparation method thereof. Background Art
[0002] In recent years, ionic two-dimensional polymer (2DP) nanosheets with unique structural and functional properties have provided a new material platform for the preparation of high-performance membranes. For example, solution-processable ultrathin 2DP nanosheets provide a new building block for the preparation of new proton exchange membranes (PEMs), which play a key role in a variety of energy conversion devices (such as fuel cells, PEM water electrolysis, etc.) and determine their comprehensive performance. Despite great progress, the preparation of continuous large-area ionic PEMs based on 2DP nanosheets has not yet been achieved, which hinders its practical application.
[0003] In general, it is quite difficult to prepare large-area ionic 2DP nanosheet membranes and maintain their integrity. On the one hand, the inherent characteristics of ionic 2DP nanosheets may bring some limitations to the assembly process. It is well known that the rigid structure of 2DP nanosheets makes it easy to crack when the membrane area increases. In addition, the large number of ionic groups connected by covalent bonds on 2DP nanosheets will produce electrostatic repulsion, thereby reducing the interaction between adjacent 2DP nanosheets, resulting in difficulty in assembling large-area membranes and instability under aqueous environmental conditions. On the other hand, most of the reported 2DP nanosheet-based membranes are prepared by vacuum-assisted self-assembly methods, which greatly limits the area size of the membrane. Fortunately, the booming development of layered membranes based on multifunctional two-dimensional nanosheets (such as graphene oxide, MXene, etc.) provides important inspiration. The intercalation strategy has been proven to be an effective method to enhance the interaction between adjacent two-dimensional nanosheets, further adjust the physicochemical structure of layered membranes, and achieve ideal comprehensive performance. Therefore, the construction of intercalated membranes is expected to largely solve the above-mentioned preparation problems of large-area 2DP nanosheet ionic membranes. The key to this method is to screen or synthesize suitable intercalants, which can enhance the interfacial interactions between adjacent nanosheets while making the membrane flexible, ultimately preparing a large-area 2DP-polyelectrolyte composite PEM with both high stability and excellent proton conductivity. Summary of the invention
[0004] In view of the deficiencies in the above-mentioned background technology, the present invention provides a method for preparing a large-area two-dimensional polymer nanosheet-based proton exchange membrane, and the prepared 2DP-polyelectrolyte composite membrane has excellent proton conduction performance.
[0005] In order to solve the above technical problems, the present invention proposes a method for preparing a large-area two-dimensional polymer nanosheet-based ion exchange membrane, which is prepared according to the following steps: Step 1, preparation of ionic 2DP nanosheet solution: weigh a certain amount of aldehyde monomer and amine monomer, wherein the molar ratio of aldehyde monomer to amine monomer is 1:1.5, then add a certain amount of solvent, stir at 25°C for 24 hours, then add a certain amount of deionized water, and stir until the solution is clear and transparent. The resulting solution is recorded as solution A; Step 2, preparation of polyelectrolyte solution: weigh the polyelectrolyte in a ratio of 0.1 to 0.4:1 of the mass ratio of the polyelectrolyte to the ionic 2DP nanosheet solution, add the polyelectrolyte to a suitable solvent, and perform ultrasonication until the polyelectrolyte is completely dissolved, which is recorded as solution B; Step 3, preparation of a large-area 2DP-polyelectrolyte composite membrane: adding the solution B obtained in step 2 to the solution A obtained in step 1, ultrasonicating until the mixture is uniformly mixed, the mixed solution is recorded as solution C, taking 120 mL of solution C and dropping it on the mold, heating it at 60° C. until it is completely dry, thereby obtaining a large-area 2DP-polyelectrolyte composite membrane attached to the glass substrate; Step 4. Post-treatment of large-area 2DP-polyelectrolyte composite membrane: The large-area 2DP-polyelectrolyte composite membrane attached to the glass substrate prepared in step 3 is first soaked in deionized water, the membrane is peeled off from the glass substrate, and then the self-supporting membrane is soaked in 1M H2SO4 solution for acidification for 24 hours, and then the composite membrane is soaked in deionized water, during which the water is changed until it is neutral, to obtain a self-supporting large-area 2DP-polyelectrolyte composite membrane.
[0006] Furthermore, the preparation method of the present invention, wherein: In step 1, the aldehyde monomer is any one of ternary aldehyde monomers such as 1,3,5-tri(p-formylphenyl)benzene, 1,3,5-tri(3'-formyl-4'-hydroxybenzene)benzene, 1,3,5-tri(4'-formyl[1,1'-biphenyl]-4-yl)benzene, trimesic acid, 2-hydroxy-1,3,5-benzenetricarbaldehyde, 1,3-dihydroxy-2,4,6-triformylbenzene, trialdehyde phloroglucinol, 1,3,5-trimethoxy-2,4,6-triformylbenzene, and 2,4,6-trichloro-1,3,5-benzenetricarbaldehyde.
[0007] In step 1, the amine monomer includes any one of diamine monomers such as 2,5-diaminobenzenesulfonic acid, p-phenylenediamine-2,5-disulfonic acid, 2,5-diaminobenzoic acid, 2,5-diaminoterephthalic acid, 2,2'-benzidine disulfonic acid, 4,4'-diamino-3,3'-biphenyl disulfonic acid, and 4,4'-diaminostilbene-2,2'-disulfonic acid.
[0008] In step 1 and step 2, the solvent includes any one of dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, and deionized water.
[0009] In step 2, the mass ratio of the polyelectrolyte to the ionic covalent organic polymer is preferably 0.1-0.4.
[0010] In step 3, the mixed solution is ultrasonicated for 10-20 min; the mold used is a glass plate of 20×20 cm or larger.
[0011] The large-area 2DP-polyelectrolyte composite membrane of the present invention has a proton conductivity of 802 mS cm at 70°C and 95% relative humidity. -1 .
[0012] Compared with the prior art, the present invention has the following beneficial effects: The present invention adopts the intercalation agent method to use ionic 2DP nanosheets as the main membrane material, add ionic polyelectrolyte as the intercalation agent, and prepare a large-area PEM by casting after sufficient mixing. The preparation method is convenient, simple, controllable and easy to operate. The prepared large-area 2DP-polyelectrolyte composite PEM has a large size (400cm 2 ), excellent stability and extremely high proton conductivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 This is a scanning electron microscope surface image of the large-area 2DP-polyelectrolyte composite membrane of Example 1.
[0014] Figure 2 This is a scanning electron microscope cross-sectional image of the large-area 2DP-polyelectrolyte composite membrane of Example 1.
[0015] Figure 3 This is a graph of the proton conductivity of the large-area 2DP-polyelectrolyte composite membrane of Example 1 at different temperatures.
[0016] Figure 4 Schematic diagram of the process for preparing a large-area 2DP-polyelectrolyte composite membrane in Example 1. DETAILED DESCRIPTION
[0017] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments. However, the following examples are only for illustration and should not be considered as any limitation to the present invention.
[0018] The preparation method of the large-area two-dimensional polymer nanosheet-based proton exchange membrane of the present invention is carried out in the following manner: 2DP nanosheets are used as the main body, polyelectrolyte is added as an intercalation agent, and the mixture is fully mixed and prepared by a casting method. The preparation process mainly includes: preparation of ionic 2DP nanosheet solution, preparation of polyelectrolyte solution, preparation of large-area 2DP-polyelectrolyte composite membrane and post-treatment of the composite membrane. The present invention adopts the method of polyelectrolyte intercalation, and the mechanical properties of the membrane and its proton conduction ability are improved by strengthening the multiple interactions between the 2DP nanosheets and further improving the content of the conductive groups in the membrane. The preparation method of the present invention is mild, controllable, simple and easy to scale up, and the prepared composite membrane has good stability and excellent proton conductivity, which is conducive to its application in fuel cells. Example 1
[0019] A method for preparing a large-area two-dimensional polymer nanosheet-based ion exchange membrane, the steps are as follows: Step 1, preparation of ionic 2DP nanosheet solution: weigh 563.4 mg of trialdehyde phloroglucinol and 1821.6 mg of 2,2'-benzidine disulfonic acid, wherein the molar ratio of trialdehyde phloroglucinol to 2,2'-benzidine disulfonic acid is 1:1.5, then add 180 mL of dimethyl sulfoxide, stir at 25°C for 24 hours, then add 36 mL of deionized water, stir for 24 hours until the solution becomes clear, to obtain an ionic 2DP nanosheet solution.
[0020] Step 2, preparation of polyelectrolyte solution: according to the optimal mass ratio of sodium poly(p-styrene sulfonate) to ionic covalent organic polymer of 0.3:1, 87.6 mg of sodium poly(p-styrene sulfonate) was weighed and added into 96 mL of deionized water, and ultrasonicated until completely dissolved to obtain a polyelectrolyte solution.
[0021] Step 3: Add the polyelectrolyte solution obtained in step 2 to the ionic 2DP nanosheet solution obtained in step 1, mix them in a volume ratio of 4:1, and ultrasonicate for 12 minutes until they are fully mixed. The mixed solution is recorded as solution C. Take 120 mL of solution C and drop it on a 20×20 cm square glass plate, and heat it in an oven at 60°C for 36 hours until it is completely dry. A large-area 2DP-polyelectrolyte composite membrane attached to the glass substrate is obtained, and its cross section is as follows: Figure 2 As shown, the surface Figure 1 shown.
[0022] Step 4: Soak the large-area 2DP-polyelectrolyte composite membrane attached to the glass substrate prepared in step 3 in deionized water first, peel the membrane from the glass substrate, and then soak the self-supporting membrane in 1M H2SO4 solution for acidification for 24 hours, and then soak the composite membrane in deionized water for 48 hours, changing the water until it is neutral, to obtain a self-supporting large-area 2DP-polyelectrolyte composite membrane.
[0023] The proton conductivity of the large-area 2DP-polyelectrolyte composite membrane was tested using an electrochemical workstation. At 70°C and 95% relative humidity, the proton conductivity was 802 mS cm -1 ,like Figure 3 shown. Example 2
[0024] The large-area two-dimensional polymer nanosheet-based ion exchange membrane was prepared. The preparation process was basically the same as that in Example 1, except that: In step 3, 3 g of sulfonated polyethersulfone was weighed and added to 45 mL of dimethyl sulfoxide, and solution D was obtained after ultrasonic dissolution. Then, solution D was added to solution C obtained in step 3 at a volume ratio of 1:1, and ultrasonic mixing was performed for 10 minutes. Subsequently, the mixed solution was dripped onto a 20×20 cm square glass plate, and heated and dried in an oven at 60°C to obtain a large-area 2DP-polyelectrolyte composite membrane attached to the glass substrate.
[0025] In summary, the present invention provides a large-area 2DP nanosheet-based ion exchange membrane, which uses ionic 2DP nanosheets as the main membrane material, adds ionic polyelectrolytes as intercalation agents, and is fully mixed and prepared by a casting method to obtain a large-area PEM. The preparation method of the present invention is mild, controllable, simple and easy to scale up. The prepared large-area 2DP nanosheet-based ion exchange membrane has excellent stability and excellent proton conductivity. At 70°C and 95% relative humidity, the proton conductivity is 802mS cm -1 .
[0026] Although the present invention has been described above in conjunction with the accompanying drawings, the present invention is not limited to the above-mentioned specific embodiments, which are merely illustrative rather than restrictive. Under the guidance of the present invention, ordinary technicians in this field can make many modifications without departing from the purpose of the present invention, all of which are within the protection of the present invention.
Claims
1. A method for preparing a large-area two-dimensional polymer nanosheet-based ion exchange membrane, characterized in that: The 2DP nanosheets are used as the main body, polyelectrolyte is added as the intercalation agent, and the mixture is fully mixed and prepared by a casting method; the details are as follows: Firstly, aldehyde monomer and amine monomer were used as raw materials to synthesize ionic 2DP nanosheet solution by step-by-step single-phase polymerization method; then, polyelectrolyte was dissolved in an appropriate amount of solvent and fully mixed with the above ionic 2DP nanosheet solution in a certain volume ratio, and finally 2DP-polyelectrolyte composite membrane was prepared by casting method.
2. The method for preparing a large-area two-dimensional polymer nanosheet-based ion exchange membrane according to claim 1, characterized in that: The aldehyde monomer includes one of 1,3,5-tri(p-formylphenyl)benzene, 1,3,5-tri(3'-formyl-4'-hydroxybenzene)benzene, 1,3,5-tri(4'-formyl[1,1'-biphenyl]-4-yl)benzene, trimesic acid aldehyde, 2-hydroxy-1,3,5-benzenetricarbaldehyde, 1,3-dihydroxy-2,4,6-triformylbenzene, triformylphloroglucinol, 1,3,5-trimethoxy-2,4,6-triformylbenzene, and 2,4,6-trichloro-1,3,5-benzenetricarbaldehyde.
3. The method for preparing a large-area two-dimensional polymer nanosheet-based ion exchange membrane according to claim 1, characterized in that: The amine monomer includes one of 2,5-diaminobenzenesulfonic acid, p-phenylenediamine-2,5-disulfonic acid, 2,5-diaminobenzoic acid, 2,5-diaminoterephthalic acid, 2,2'-benzidine disulfonic acid, 4,4'-diamino-3,3'-biphenyl disulfonic acid, and 4,4'-diaminostilbene-2,2'-disulfonic acid.
4. The method for preparing a large-area two-dimensional polymer nanosheet-based ion exchange membrane according to claim 1, characterized in that: The polyelectrolyte is one or more of sodium poly(p-styrene sulfonate), sulfonated polyether sulfone, sulfonated polyether ether ketone, sulfonated polybenzimidazole, sulfonated polyimide, sulfonated polyvinyl alcohol and perfluorosulfonic acid.
5. The method for preparing a large-area two-dimensional polymer nanosheet-based ion exchange membrane according to claim 1, characterized in that: The specific steps include: Step 1, preparation of ionic 2DP nanosheet solution: weigh a certain amount of aldehyde monomer and amine monomer, wherein the molar ratio of aldehyde monomer to amine monomer is 1:1.5, then add a certain amount of solvent, stir at 25°C for 24 hours, then add a certain amount of deionized water, and stir until the solution is clear and transparent. The resulting solution is recorded as solution A; Step 2, preparation of polyelectrolyte solution: weigh the polyelectrolyte in a ratio of 0.1 to 0.4:1 of the mass ratio of the polyelectrolyte to the ionic 2DP nanosheet solution, add the polyelectrolyte to a suitable solvent, and perform ultrasonication until the polyelectrolyte is completely dissolved, which is recorded as solution B; Step 3, preparation of large-area 2DP-polyelectrolyte composite membrane: adding solution B obtained in step 2 to solution A obtained in step 1, ultrasonicating until the mixture is uniformly mixed, the mixed solution is recorded as solution C, taking 120 mL of solution C and dropping it on a glass mold, heating it at 60° C. until it is completely dry, thereby obtaining a large-area 2DP-polyelectrolyte composite membrane attached to the glass substrate; Step 4. Post-treatment of large-area 2DP-polyelectrolyte composite membrane: The large-area 2DP-polyelectrolyte composite membrane attached to the glass substrate prepared in step 3 is first soaked in deionized water, the membrane is peeled off from the glass substrate, and then the self-supporting membrane is soaked in 1M H2SO4 solution for acidification for 24 hours, and then the composite membrane is soaked in deionized water, during which the water is changed until it is neutral, to obtain a self-supporting large-area 2DP-polyelectrolyte composite membrane.
6. The method for preparing a large-area two-dimensional polymer nanosheet-based ion exchange membrane according to claim 5, characterized in that: In step 1 and step 2, the solvent includes one or more of dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, and deionized water.
7. The method for preparing a large-area two-dimensional polymer nanosheet-based ion exchange membrane according to claim 5, characterized in that: In step 2, the mixed solution is sonicated for 10-20 min.
8. The method for preparing a large-area two-dimensional polymer nanosheet-based ion exchange membrane according to claim 5, characterized in that: The glass mold in step 3 is a glass plate of 20×20 cm or larger size.
9. A large-area two-dimensional polymer nanosheet-based ion exchange membrane, characterized in that The preparation is carried out by the preparation method according to any one of claims 1 to 8.
Citation Information
Patent Citations
Preparation method of two-dimensional porous precious metal-base nano-catalyst
CN107086314A
Method for preparing two-dimensional covalent organic framework ultrathin nanosheet material composite film and application of two-dimensional covalent organic framework ultrathin nanosheet material composite film
CN112973468A
Tannic acid bonded covalent organic framework composite proton exchange membrane and preparation method thereof
CN116655972A
Composite polymer electrolytes for proton exchange membrane fuel cells
EP1665438A1
Cited By
Flexible anti-static high-temperature-resistant FDC special film and preparation method thereof
CN120310258A
Reverse stacking TF-PA-COOH COF material and preparation method and application thereof
CN121574325A
